Strategi Pembinaan Dan Pengembangan Ekstrakurikuler Pendidikan Agama Islam Di Sekolah Menengah Kejuruan Negeri 1 Batang Tahun 2016 - Hidayat, Falahuddin; , Dr. Sabar Narimo, M.M, M.Pd; , Dr. M. Muhtarom, SH. MH (2016)
Education in schools generally organize two activities, namely intra-curricular and extracurricular. Intrakurikuler is the activity of formal education in schools, meaning that both activities, educational objectives, content and teaching materials, as well as the method of presentation has been made clearly and poured in a set of rules or a handle that has been validated. While extracurricular educational activities are outside of subjects. Extracurricular Islamic Religious Education in school is the learning activities of Islamic education is done outside school hours intrakurikuler, held in the school or outside the school in an effort fostering religious to expand the knowledge, insight, ability, improve and apply the value of the knowledge and skills that have been learned intra-curricular activities. Ektrakulikuler Islamic Education is expected to fortify and prepare students in the era of globalization.This research uses descriptive qualitative research design. Qualitative description is basically observing people in everyday life with a reasonable situation, interact with them, doing interviews and trying to make sense of language, habits, and behaviors associated with the research focus The results showed that the strategy of development and extracurricular educational development of Islam in SMK N 1 Batang, to use new member coaching strategies and coaching program. Streategi development through evaluation, socialization, and KIAS approach. Obstacles encountered include: lack of infrastructure, the active role of teachers and parents, students' awareness.